Benthic mollusc assemblages in subtidal coastal waters of Penang National Park, Malaysia - Alianie Mustaffa; Omar Ahmad; Vararin Vongpanich; Anita Talib; Khairun Yahya (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Benthic molluscs were sampled bimonthly from October 2010 to September 2011. Four sampling sites were selected (Teluk Bahang, Teluk Aling, Teluk Ketapang and Pantai Acheh) based on difference human activities in surrounding coastal waters of Penang National Park. Sampling activities were done starting at 200 m from the subtidal shoreline until 1200 m offshore. A total of 432 benthos samples were collected using 6’ X 6’ Ponar grab. From this study, 25 species from 21 families and 25 genera were identified. Particle size analysis was done and revealed Penang National Park coastal waters is a muddy area with more than 80% of the sediment samples diagnosed as mud. Whereas, in Teluk Bahang and Teluk Aling, the starting transects (200 m to 400 m) were consisted mixture of particle size but the proportion of particle size gradually changed to mud towards the shore. Based on Pearson’s Correlation, it was found that Nuculanidae, Megastomia sp., and Timoclea sp. showed positive correlations with sandy particles (1000 ;m-250 ;m) with r values ranging 0.88 to 0.96 at p0.01. The density of benthic molluscs was found highest in Teluk Bahang followed by Teluk Aling, Teluk Ketapang and Pantai Acheh with overall mean value 613.6 molluscs/m2. Penang National Park coastal waters are all considered shallow as the depth never exceeding 10 m.